Membrane Glycerolipid Remodeling Triggered by Nitrogen and Phosphorus Starvation in Phaeodactylum tricornutum. Issue 1 (8th December 2014) - Abida, Heni; Dolch, Lina-Juana; Meï, Coline; Villanova, Valeria; Conte, Melissa; Block, Maryse A.; Finazzi, Giovanni; Bastien, Olivier; Tirichine, Leïla; Bowler, Chris; Rébeillé, Fabrice; Petroutsos, Dimitris; et al.
Abstract : Nitrogen and phosphorus limitations trigger distinct remodeling processes and adaptive responses at the level of membrane and storage glycerolipids in a marine model diatom . Abstract: Diatoms constitute a major phylum of phytoplankton biodiversity in ocean water and freshwater ecosystems. They are known to respond to some chemical variations of the environment by the accumulation of triacylglycerol, but the relative changes occurring in membrane glycerolipids have not yet been studied. Our goal was first to define a reference for the glycerolipidome of the marine model diatom Phaeodactylum tricornutum, a necessary prerequisite to characterize and dissect the lipid metabolic routes that are orchestrated and regulated to build up each subcellular membrane compartment. By combining multiple analytical techniques, we determined the glycerolipid profile of P. tricornutum grown with various levels of nitrogen or phosphorus supplies. In different P. tricornutum accessions collected worldwide, a deprivation of either nutrient triggered an accumulation of triacylglycerol, but with different time scales and magnitudes. We investigated in depth the effect of nutrient starvation on the Pt1 strain (Culture Collection of Algae and Protozoa no. 1055/3). Nitrogen deprivation was the more severe stress, triggering thylakoid senescence and growth arrest. By contrast, phosphorus deprivation induced a stepwise adaptive response. The time scale of the glycerolipidome changes and the comparison with large-scale transcriptome studies were consistent with an exhaustion of unknown primary phosphorus-storage molecules (possibly polyphosphate) and a transcriptional control of some genes coding for specific lipid synthesis enzymes. We propose that phospholipids are secondary phosphorus-storage molecules broken down upon phosphorus deprivation, while nonphosphorus lipids are synthesized consistently with a phosphatidylglycerol-to-sulfolipid and a phosphatidycholine-to-betaine lipid replacement followed by a late accumulation of triacylglycerol.